A review of flexibility options for high RES penetration in power systems — Focusing the Greek case. (November 2021) - Alexopoulos, Dimitrios K.; Anastasiadis, Anestis G.; Vokas, Georgios A.; Kaminaris, Stavros D.; Psomopoulos, Constantinos S.
Abstract: Applying the Renewable Energy Directive 2009/28/EC in Greece, Renewable Energy Sources (RES) share in gross final consumption (GFC) of energy should reach at least 18% by 2020. Subsequently, according to the Greek National Energy and Climate Plan (NECP), the RES share in GFC of energy must reach at least 35% by 2030 and the RES share in the GFC of electricity must reach at least 61%, respectively. Based on estimates it was found that installed capacity of at least 9 GW of Renewable Energy (RE) power plants is needed to achieve the above milestones. The installed capacity of variable RE (vRE) power plants (wind and photovoltaic power plants) in Greece during 2017–2030 is expected to be tripled. To achieve such high penetration of variable RES (vRES) in the power systems flexibility issues and needs inevitably arise. System operators seek to identify the most suitable flexibility options combination to meet the challenges posed by high penetration of vRES in the power systems. This paper reviews the different flexibility options (e.g. demand response, energy storage, power to X, supply side etc.) that exist and are tools for the transitioning into a flexible power system. In addition, twenty-three (23) different flexibility options are described and twelve (12) quantitative (numerical) and qualitative parameters are considered. For each of these parameters, data have been obtained from an extensive literature review. Focusing the Greek energy system as an example, all options and parameters are further analyzed presenting their technical characteristics, their economic, technical, and social barriers as well as their environmental impacts in order to assess which flexibility options are most suitable for the Greek power system for the optimization of RES penetration.